Penerapan Model Pembelajaran Sinektik untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Madrasah Tsanawiyah - Daswa Daswa (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2015)
ABSTRACT This study aims to solve the problem of lack of creative thinking ability used sinektik learning model. This research is a quasi-experimental design with a control group of non-equivalence. The subjects in this study were students of MTs Husnul Khotimah Kuningan VIII class are divided into two groups: the experimental group as many as 31 students and a control group as many as 33 students. The experimental group get sinektik learning model, while the control group getting conventional learning models. Collecting data using the research results in the form of test instruments of creative thinking ability. Data were analyzed quantitatively and qualitatively. Data pretest and posttest of creative thinking ability processed with SPSS 16 for windows. The results showed that an increase in creative thinking abilities of students who study mathematics learning model sinektik better than students who use conventional learning model.                                                                                                          Keywords: sinektik learning model, the ability creative thinking.